Understanding artificial optical magnetism of periodic metal-dielectric-metal layered structures - C. Tserkezis; N. Papanikolaou; G. Gantzounis; N. Stefanou (Physical Review B, 2008)
Plasmonic excitations in two- and three-dimensional ordered assemblies of metal-dielectric-metal nanosandwiches are studied by means of full-electrodynamic calculations using the layer-multiple-scattering method. Plasmon hybridization results in collective electric-dipole-like and magnetic-dipole-like resonant modes, which are directly controlled by the lattice constant and the geometrical characteristics of the building units. It is shown that, in planar arrays of such composite nanoparticles on a dielectric substrate, the magnetic resonance induces a negative effective permeability, as large as −2  , which can be tuned within the range of near-infrared and visible frequencies. However, as successive layers are stacked together to build a three-dimensional crystal, the region of negative effective permeability shrinks and disappears for relatively thick slabs. Our analysis demonstrates that the complex photonic band structure is a valuable tool in the study of three-dimensional metamaterials and their effective-medium description.